2021
DOI: 10.1111/resp.14006
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial coil spring fiducial markers for CyberKnife® stereotactic body radiation therapy

Abstract: We assessed for the first time the safety and efficacy of bronchoscopically inserted cs‐FM for CyberKnife® SBRT delivery. We show that this technique is safe and resulted in a very high PPL tracking rate enabling optimal SBRT delivery. See Cover Image See related https://onlinelibrary.wiley.com/doi/full/10.1111/resp.14040

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Smaller case series have examined endobronchial and endovascular FM placement as alternatives to percutaneous FM placement [ 25 , 29 , 30 ]. Mongeon et al [ 25 ] compared endovascular FM placement with percutaneous placement and reported no complications associated with endovascular marker insertion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smaller case series have examined endobronchial and endovascular FM placement as alternatives to percutaneous FM placement [ 25 , 29 , 30 ]. Mongeon et al [ 25 ] compared endovascular FM placement with percutaneous placement and reported no complications associated with endovascular marker insertion.…”
Section: Discussionmentioning
confidence: 99%
“…However, endovascular marker placement is challenging and was recommended for patients ineligible for percutaneous FM implantation. Casutt et al [ 29 ] reported one complication (bronchospasm) among 55 EBUS-guided FM implantation procedures and concluded that the low rate of concurrent transbronchial biopsies may have contributed to the absence of pneumothorax. Majid et al [ 30 ] also inserted FM via EBUS and reported a complication rate of 5.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication in Respirology , Casutt et al . have utilized fluoroscopy with or without radial endobronchial ultrasound (R‐EBUS) to localize the peripheral pulmonary lesion 7 . With this technique, the tumour can be localized with R‐EBUS but then requires removal of the ultrasound probe in order to insert the fiducial marker.…”
mentioning
confidence: 99%
“…They have utilized 0.018 in. fibred platinum coils that have been designed for endovascular embolization 7 . The coils have atraumatic tips and form a conical shape when deployed with the apex of the cone being deployed first.…”
mentioning
confidence: 99%